Quality of life among patients with chronic non-communicable diseases during COVID-19 pandemic in Southern Ethiopia: A cross-sectional analytical study - Ayalew, Mohammed; Deribe, Bedilu; Hussen, Siraj; Defar, Semira; Gedefaw, Abel (Frontiers in Psychiatry, 2022)
Background: The COVID-19 outbreak became a continuing global health agenda. It has a significant impact on individuals’ quality of life (QOL). Patients with pre-existing medical conditions may have severely reduced QOL. The aim of this study was to assess QOL and its associated factors among patients with chronic non-communicable diseases (NCDs) during COVID-19 pandemic at Sidama regional state, southern Ethiopia. Methods: We conducted a multicenter, cross-sectional study from June 1 to September 1, 2021. A total of 633 participants took part in the study, using an interviewer-administered structured questionnaire. The QOL was measured using the World Health Organization Quality of Life (WHOQOL-BREF) scale, which has 12 items. To describe different variables, descriptive statistics were employed. To find independent factors associated with QOL, we used multivariable linear regression analysis. A P-value of <0.05 was declared statistically significant at 95% confidence interval (CI). Results: The majority (56.4%) of participants were male and about half (53.1%) had a diagnosis of diabetes mellitus. The multivariable linear regression model showed statistically significant negative association between different independent variables such as age (β= -0.188, 95% CI = -0.238 to -0.139), being female (β= -1.942, 95% CI = -3.237 to -0.647), duration of illness ≤5 years (β= -4.222, 95% CI = -6.358 to -2.087), alcohol use in the past 3 months (β= -4.574, 95% CI = -6.905 to -2.243), common mental disorder (CMD) (β= -1.512, 95% CI = -2.924 to -0.100), insomnia (β= -0.274, 95% CI = -0.380 to -0.168) and QOL. Also, there is a statistically significant positive association between QOL and being illiterate (β= 3.919, 95% CI = 1.998 to 5.841) and living in rural area (β= 2.616, 95% CI = 1.242 to 3.990). Conclusions: In general, the findings confirmed that the COVID-19 pandemic had a negative impact on patients with chronic NCDs QOL. QOL was significantly influenced by age, gender, educational status, residence area, duration of illness, alcohol use, CMD, and insomnia during COVID-19 pandemic. Thus, this study suggests that addressing insomnia, co-morbidities of mental disorders, and alcohol use have the potential effect to improve QOL of patients with chronic medical illnesses.